Cage Polyamine Molecule Hexamethylenetetramine as Additives for Improving Performance of Perovskite Solar Cells. Issue 3 (11th January 2023) - Tian, Jingxu; Wu, Jihuai; Lin, Yuhe; Geng, Jialian; Shi, Jialiang; Lin, Wenhui; Hao, Wenxuan; Ke, Chaoran; Yang, Jinhui; Sun, Weihai; Lan, Zhang
Abstract : As a rising star in the photovoltaic field, perovskite solar cells (PSCs) have attracted extensive attention. However, the industrialization development of PSCs still faces the dual challenges of improving efficiency and stability. Herein, a cage polyamine molecule hexamethylenetetramine (HMTA) as additive is incorporated into the tin oxide electron transport layer (ETL). The introduction of HMTA improves the electron extraction ability of SnO2 and optimizes the energy‐level alignment of function layers. The modification of HMTA also passivates the uncoordinated Pb 2+ in the perovskite and reduces the oxygen vacancy defects of SnO2, which alleviate trap‐state density and carrier nonradiative recombination. As a result, the PSC based on the SnO2 ETL modified with HMTA achieves a high power conversion efficiency of 22.37% along with good stability. The research results demonstrate a typical case of using cage polyamines to improve the performance and stability of PSCs. Abstract : A cage polyamine molecule hexamethylenetetramine as additive is incorporated into the SnO2 electron transport layer of perovskite solar cells, which improves the electron extraction ability of SnO2, optimizes the energy‐level alignment of function layers, passivates, and reduces the defects of SnO2 . As a result, the modified device achieves a high power conversion efficiency of 22.37% along with good stability.